Essential Information Sharing Thresholds for Reducing Market Power in Financial Access: A Study of the African Banking Industry - Simplice Asongu; Sara Le Roux; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2016)
This study investigates the role of information sharing offices (public credit registries and private credit bureaus) in reducing market power for financial access in the African banking industry. The empirical evidence is based on a panel of 162 banks from 42 countries for the period 2001-2011. Three simultaneity-robust empirical strategies are employed, namely: (i) Two Stage Least Squares with Fixed Effects in order to account for simultaneity and the observed heterogeneity; (ii) Generalised Method of Moments (GMM) to control for simultaneity and time-invariant omitted variables and (iii) Instrumental Variable Quantile regressions to account for simultaneity and initial levels of financial access. In order to ensure that information sharing offices influence market power for loan price (quantity) to decrease (increase), public credit registries should have between 3.156% and 3.3% coverage, while private credit bureaus should have between 1.443 and 18.4% coverage. The established thresholds are cut-off points at which information sharing offices completely neutralise the negative effect of market power on financial access. The thresholds are contingent on the dimension (loan price versus loan quantity) and distribution (conditional mean versus conditional distribution) of financial access.
Keywords: G20; G29; L96; O40; O55; 330; Financial access; Market power; Information sharing